Geographic pattern of the prevalence of intimate partner violence against women in Zanjan (Iran) - Karamitanha, Farzaneh; Ahmadi, Farzane; Fallah Abadi, Vahid (Frontiers in Psychology, 2024)
Introduction Intimate partner violence (IPV) against women is a serious public health issue and refers to physically, sexually and psychologically harmful behaviors as well as emotionally controlling behaviors and financial abuse that occur in the form of marriage or cohabitation. Knowing the current situation of the IPV prevalence against women and high-risk areas in the Zanjan city, Iran, can help policymakers to establish better health programs for risk reduction. Methods This population-based cross-sectional study consisted of married women aged 18–55 years living in Zanjan city in 2021. 760 married women covered by 19 urban comprehensive health service centers (UCHSCs) were selected by the stratified systematic random sampling method. The prevalence of IPV against women was measured in four types: psychological, physical, sexual, and economic. Results Mean (SD) age of the women was 35.49 (8.76) years. 606 women (79.7%) experienced one type of IPV. The highest and lowest IPV prevalence against women were psychological (76.6%) and economic (12%), respectively. The highest and lowest prevalence of psychological violence were observed in CUHSCs 2 and 17, physical violence in CUHSCs 1 and 14, sexual violence in CUHSCs 2 and 17, and economic violence in CUHSCs 2 and 8, respectively. The severity of violence was higher among self-employment or workers husbands, with low monthly household income, and among younger women. Discussion The IPV rate in the target population is high, and the highest rate is related to psychological violence. These results highlight the need to intervention in the society and high-risk women for policymakers of the health system.